A REVIEW OF INNOVATIVE TECHNOLOGIES FOR THE DIAGNOSIS AND TREATMENT OF CARIES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This work examines modern methods of diagnosing and treating dental caries: a review of innovative technologies is provided, with examples of instrumental diagnostic methods. A comparison between them is made, considering the advantages and disadvantages of each method.